2021
DOI: 10.1038/s41598-021-82371-5
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that spillover from Marine Protected Areas benefits the spiny lobster (Panulirus interruptus) fishery in southern California

Abstract: Marine Protected Areas (MPAs) are designed to enhance biodiversity and ecosystem services. Some MPAs are also established to benefit fisheries through increased egg and larval production, or the spillover of mobile juveniles and adults. Whether spillover influences fishery landings depend on the population status and movement patterns of target species both inside and outside of MPAs, as well as the status of the fishery and behavior of the fleet. We tested whether an increase in the lobster population inside … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 57 publications
0
54
0
Order By: Relevance
“…However, research has shown that localised sheries yield can increase as a result of ARs, through increased production of commercial species 89, 90 , as well as MPA establishment, as a result of the 'spillover effect', as described and demonstrated by 91,92 . Some interviewees discussed this, such as I1, who said "[because of the MPA and conservation work] sh have come back to the area, particularly sh that are commonly consumed by local people, such as snapper sh.…”
Section: Changes In Shing Yieldmentioning
confidence: 99%
“…However, research has shown that localised sheries yield can increase as a result of ARs, through increased production of commercial species 89, 90 , as well as MPA establishment, as a result of the 'spillover effect', as described and demonstrated by 91,92 . Some interviewees discussed this, such as I1, who said "[because of the MPA and conservation work] sh have come back to the area, particularly sh that are commonly consumed by local people, such as snapper sh.…”
Section: Changes In Shing Yieldmentioning
confidence: 99%
“…Conservation acts include setting up regional freshwater conservation reserves or MPAs (Koning & McIntyre, 2021;Lenihan et al, 2021), or globally, the Convention on Biological Diversity. In situ conservation zones such as small grassroots reserves in the Mekong River systems (Koning & McIntyre, 2021) are usually localized and isolated, yet are important in protecting food webs and augmenting fisheries yields.…”
Section: Strategies For Conservation Of Genetic Resourcesmentioning
confidence: 99%
“…
The importance of conservation of aquatic biodiversity on sustainable fisheries is gradually being recognized by more and more people. Positive results have been reported from establishing marine protected areas (MPAs) as well as freshwater reserves (Koning & McIntyre, 2021;Lenihan et al, 2021). Conservation of aquatic animals and plants is not yet fully addressed in a way that will protect genetic resources for aquaculture purposes.
…”
mentioning
confidence: 99%
“…After the establishment of a MPA in an intensely-fished area, the biomass and body size of the target species generally increases through time within MPA boundaries (Halpern and Warner 2002;Harmelin-Vivien et al 2008). Other metrics like fish abundance and species richness may also increase (Vanderklift et al 2013), although such effects appear less general and more idiosyncratic than recovery of exploited species biomass, and are generally not considered as unequivocal indicators of MPA effectiveness Lenihan et al 2021).…”
Section: Introductionmentioning
confidence: 99%